Comparative Analysis of Financial Ratios in Evaluating Financial Performance Pre- and Post-IPO on the IDX (Case Study of PT Bukalapak TBK and PT Goto Gojek Tokopedia TBK, 2020–2024) - Sildy, Aptia; Ichwani, Tia (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to conduct a comparative analysis of the financial ratios and financial performance of PT Bukalapak Tbk and PT Gojek Tokopedia Tbk during the periods before and after their Initial Public Offering (IPO) on the Indonesia Stock Exchange from 2020 to 2024. Utilizing a quantitative method with a descriptive-comparative and associative approach, financial performance is assessed through the Financial Performance Index (IKK), which integrates dimensions of liquidity, profitability, and solvency. The findings indicate that the implementation of the IPO has a significant positive impact, evidenced by the increase in Cash Ratio (CaR), Return on Equity (ROE), and Net Profit Margin (NPM) in the post-IPO period compared to the pre-IPO period. The IKK trends for both companies demonstrate structural improvements following their listing on the stock exchange, with the post-IPO IKK consistently positioned above the pre-IPO period. Correlation and regression tests confirm that profitability and liquidity are the primary drivers of enhanced financial performance, while the combination of these three ratio dimensions effectively explains the variation in IKK within this research model.